PENGARUH PROFITABILITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR INDUSTRI BAHAN DASAR KIMIA DI BURSA EFEK INDONESIA 2019-2021 - Nabhilla Fraynceni; Debora Tambunan; Ahmad Rivai (Jurnal Mahkota Bisnis (Makbis), 2023)
This study aims to examine the effect of Profitability, Leverage and company size on earnings management in manufacturing companies in the Chemical Materials Sub-Sector on the Indonesia Stock Exchange 2019-2021. The population in this study were 34 Chemical Materials Industry companies on the Indonesia Stock Exchange 2019-2021. This study used purposive sampling and obtained a sample of 12 companies. The sample collection technique used the purposive sampling method, namely taking research samples by considering several specific criteria based on the research objectives. Data analysis used multiple linear regression with the help of SPSS software. The results of the determination coefficient test showed that the Adjusted R2 value obtained was 0.469, which came from squaring the correlation coefficient value "R", which is 0.709 x 0.709 = 0.503. The magnitude of the determination coefficient (R Square) is 0.503 or equal to 50.3%. The figure means that the ROE, DER, and Size variables simultaneously (together) influence the Profit Management variable of Chemical companies listed on the IDX in 2019-2021